1971
DOI: 10.1149/1.2407950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Superimposed A.C. on D.C. in Electrodeposition of Ni-Fe Alloys

Abstract: The electrochemistry of a number of aminoquinones and quinone thioethers has been investigated in aqueous-ethanol solutions. Half-wave potentials as a function of pH have been measured polarographically and heterogeneous rate constants for several of the compounds have been determined by cyclic voltammetry. The E1/2's and the ks.h'S have been compared with hyperfine splitting constants determined by ESR spectrometry and conclusions arrived at as to the effect of spin density on electrochemical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Formation of Zn hydroxide film during the electrodeposition of the alloys.--There is, as yet, no theoretical explanation which satisfactorily describes the mechanism of the anomalous codeposition. Many hypothesis have been proposed so far (11)(12)(13) and one of the most plausible mechanisms included the assumption that the pH in the vicinity of the cathode was raised to permit the precipitation of metal hydroxide on the cathode (14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…Formation of Zn hydroxide film during the electrodeposition of the alloys.--There is, as yet, no theoretical explanation which satisfactorily describes the mechanism of the anomalous codeposition. Many hypothesis have been proposed so far (11)(12)(13) and one of the most plausible mechanisms included the assumption that the pH in the vicinity of the cathode was raised to permit the precipitation of metal hydroxide on the cathode (14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…However, others have found that the first roughly 1200-1500A of plate is very iron rich, usually 40-60% instead of 20% Fe (4,5). If these gradients do in fact exist in our wires (6), we feel that they could be eliminated by changes in the NiFe solution flow pattern around the wire and/or by the superposition of an a-c current on the d-c NiFe plating current (7).…”
Section: Resultsmentioning
confidence: 99%
“…The electrolytic dendritic growth Use of alternating current in deposition technolof cadmium was studied by Wranglen [101, who ogy is a familiar method of improving deposit characfound it to grow as single crystals by a sequential teristics [11. Deposit characteristics like grain size, layer growth mechanism involving two-dimensional brightness, hardness etc., are shown to be influenced nucleation for each layer. Price [11], in a study on favourably by superimposing ac during deposition vapour-grown cadmium dendrites, reported that the [2][3][4]. Morphological studies have been made in our growth occurs at re-entrancies produced by twinning.…”
Section: Introductionmentioning
confidence: 92%